Kondisi Kesehatan Karang Di Perairan Pantai Gonda, Polewali Mandar, Sulawesi Barat - Andy Nugraha; Magdalena Litaay; Willem Moka (Jurnal Ilmu Alam dan Lingkungan, 2019)
The research on "The condition of coral health in the coastal waters of the Gonda, Polewali Mandar, West Sulawesi" has been carried out in April 2018. This study aims to determine the health conditions of coral reefs in the waters of Gonda Beach, Polewali-Mandar, West Sulawesi Province, using health tables coral. Data retrieval is carried out using the "Line Intercept Transect (LIT)" method with 50-meter transect in depths of 3 m and 10 m,The parameter that observed was the colour of coral colony. Data processing is carried out by entering approximately 20 coral colonies that have been found in the entry excel coral watch that are already available with standardized data processing columns. The results of this study indicate that coral health conditions in the coastal waters of Gonda, Polewali - Mandar, West Sulawesi Province classified as in the unhealthy category. The highest percentage of coral colonies is branched coral colonies.